The Correlation Between Xreading Time Spent and Reading Comprehension & Efl College Students’ Attitudes Towards Xreading - Alvin Nuril Hidayah; Anis Trisusana (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
AbstractThis study aimed to identify the correlation between reading time in XReading and students’ academic reading comprehension and find out students’ attitudes toward XReading. A quantitative and qualitative approach were used to answer the problems. The participants of this study were first-year EFL college students who take part in extensive reading (ER) program with XReading as the assigned platform. The data were collected from the recorded time spent by students in XReading and their scores on a reading comprehension test. The test was adapted from a Reading Comprehension Test designed for advanced readers. The data were analyzed using Pearson Correlation and Linear Regression to determine how XReading contributes to reading comprehension. The results showed that reading time in XReading contributed to reading comprehension by about 10%, yet there was no significant correlation between the two variables. In addition, Likert Scale questionnaires and interviews were analyzed using a descriptive qualitative design to determine the students’ attitudes toward XReading. The results found that students have positive attitudes to XReading. Therefore, it could be concluded that ER practices using XReading can be implemented by providing and encouraging students to read more academic reading materials to develop academic comprehension